Turismo cultural e sustentabilidade da cidade de caldas novas – Goiás : uma abordagem sobre a religiosidade e suas tramas - (:unkn) unknown (Universidade Estadual de Goiás, 2018)
The tourism and the religiosity in Caldas Novas, side by side with the sustainability and the process of cultural immersion between sacred and profane, bonded with the conservation of cultural patrimony of the city and it’s residents, became a subject of plenty relevance because of it’s potentiality at the moment. The main goal of this present paperwork, was to verify how the local witch brought a legacy by it’s healing and miraculous thermal waters developed a touristic potential and, also, religious and cultural very important to the Midwest of the country. On the other hand, as the organs responsible for the growth and development of the city create all this specific sustainability in structure and maintenance to receive several visitors, not only “romeiros”, pilgrims, visits to the Paróquia Nossa Senhora das Dores and the Santuário Nossa Senhora da Salete , but people who come just to hang out, have fun and get to know the natural beauties of the place. For the accomplishment of these studies, we counted on the bibliographical and field research. Field research was carried out by the qualitative research, of an exploratory nature, with analytical-descriptive orientation, through semi-structured interviews with open questions. Its subjects were traditional families and founders of the municipality, the Bishop of the Catholic Church of the county of Ipameri, neighboring city, priests and religious of the Paróquia Nossa Senhora das Dores and Santuário Nossa Senhora da Salete, the political segment in tourism and cultural sphere, and part of the city's current population and religious tourists. The results of the research point out that the practice of religious cultural tourism together with recreation tourism is totally practicable. It establishes spaces of communion and solidarity between the individuals, helping personal and cultural growth among people. It encompasses a whole spiritual and cultural experience of the local community as well as the multiple subjects who visit the sacred places and above all the fundamental of this segment, people’s faith.
Keywords: Turismo cultural; Turismo religioso; Sustentabilidade; Preservação patrimonial; Cultural tourism; Religious tourism; Sustainability; Patrimonial preservation; CIENCIAS BIOLOGICAS; CIENCIAS SOCIAIS APLICADAS::TURISMO